Value and Efficacy of Sentinel Lymph Node Diagnostics in Patients With Penile Carcinoma With Nonpalpable Inguinal Lymph Nodes: Five-Year Follow-up. (August 2016) - Lützen, Ulf; Zuhayra, Maaz; Marx, Marlies; Zhao, Yi; Knüpfer, Stephanie; Colberg, Christian; Jünemann, Klaus-Peter; Naumann, Carsten Maik
Abstract : Purpose: Sentinel lymph node biopsy (SLNB) has been described as a minimally invasive method for lymph node staging in patients with a penile carcinoma and nonpalpable inguinal nodes in national and international guidelines of involved professional societies. However, this method is rarely used. The aim of this study was to validate reliability and morbidity of this method and to discuss radiation exposure of persons involved. Methods: Twenty-eight patients with histologically negative sentinel lymph nodes in 47 groins with nonpalpable inguinal lymph nodes were included in this study (17 T1(a/b)-, 8 T2- and 3 T3-stages). We recorded prospectively all cases of lymph node recurrence and complications in patients with initially nonpalpable inguinal lymph nodes and histologically negative sentinel lymph nodes. False-negative findings and morbidity were calculated as qualitative criteria. Inguinal regions with palpable lymph nodes and/or evidence of metastases were not considered in accordance with the guidelines. Results: During a median follow-up of 68 (4–131) months, we observed one case of bilateral lymph node recurrence and one case of prolonged inguinal lymphorrhea, which could be managed conservatively. Per inguinal region, false-negative rate was 4.25%, and morbidity rate was 2.12%; seen per patient, the rates were both 3.57%. Conclusions: Sentinel lymph node biopsy under use of radioactive tracers is a reliable method of lymph node staging in patients with penile carcinoma and nonpalpable inguinal lymph nodes. The methodical complexity is justified by high reliability and low radiation exposure for both patient and medical staff and low morbidity rates.